Diabetıc Cardiomyopathy And G Protein - Yasemin Behram Kandemir; Ünal Güntekin; Çiğdem Aydın; Gökhan Görgişen (Van Tıp Dergisi, 2019)
Diabetes mellitus (DM) is one of the most important disease in the modern society and represents not only a medical but also social problem. Cardiovascular disease is the primary cause of death in people with either type 1 or type 2 diabetes. According to WHO data, more than 75% of patients with type 2 diabetes mellitus die due to vascular accidents. It represents an important risk factor for the development of coronary disease and mortality. It increases the risk equivalent to a 2- to 4-fold greater prevalence of cardiovascular disease than do non-diabetic (ND) individuals. Patients with diabetes are prone to a diffuse and rapidly progressive form of cardiomyopathy. The precise mechanisms through which diabetes increases the likelihood of cardiomyopathy are not completely defined. In a diabetic environment certain proteins exist which are incriminated to promote the formation of cardiomyopathy. Diabetic cardiomyopathy is distinct from ischemic cardiomyopathy. One of the basic underlying causes of diabetic cardiomyopathy is that hyperglycemic condition induces vascular smooth muscle proliferation and migration at a significantly faster rate than normoglycemia. Cellular molecular mechanisms have a pivotal role in developing cardiomyopathy, the early phase of diabetic heart disease. G alpha class of G-proteins are the most important signaling changes in the development of cardiomyopathy.